(untitled) (CIPEEX, 2026)
The purpose of this study is to bring closer the encounter between art, psychoanalysis, and culture. It associates social and figurative aspects that will be discussed and analyzed through a psychoanalytic perspective based on case studies. Considering that art is one of the resources through which Freud and Lacan elaborated questions related to psychoanalytic praxis, such as anguish, the paradoxes of human satisfaction, and their effects on the spectator. Therefore, a case study will be presented, starting from the impacts of art in the cultural context and its modes of subjectivation through the psychoanalytic lens. It is expected that this project will contribute to the academic research field, aiming to bring students of the Evangelical University of Goiás closer to the psychoanalytic scientific methodology. The implications of this study propose to analyze the dialectical effects between the subject of postmodern culture and the art that symbolizes it.